DEVELOPING VOCABULARY IN YOUNG LEARNERS THROUGH PLAY-BASED LEARNING - Alwan Maulana; Ahmad Revan; Ahmad Zaenal Abidin; Selnistia Hidayani (PT. Intelek Cendikiawan Nusantara, 2025)
This study explores the role of play-based learning in developing English vocabulary among young learners. Utilizing a qualitative approach, data were gathered through classroom observations and interviews with primary school teachers. The findings reveal that play-based activities such as games, role-playing, and interactive storytelling significantly enhance vocabulary acquisition by creating a fun, engaging, and meaningful learning environment. The study highlights how play not only fosters motivation but also supports contextual learning, allowing children to naturally acquire and retain new words. Implications for classroom practices and future curriculum design are discussed.